2019
DOI: 10.3390/ma13010063
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles by Low-Energy Wet Bead Milling of Metal Spheres

Abstract: A low-energy, magnetically-driven milling technique for the synthesis of silver nanoparticles is proposed, where the grinding medium and the metal precursor consisting of silver spheres have the same shape and size, belonging to a millimetric scale. The process is carried out at room temperature in aqueous solvent, where different types of capping agents have been dissolved to damp particle agglomeration. The particle diameters, determined by dynamic light scattering and transmission electron microscopy, have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…The smallest diameters are obtained for Ag NPs stabilized with fructose, with an estimated average value of 9.5 nm, while it amounts to 11.1 nm for mannitol-capped Ag NPs. Both values are comparable with those obtained in another study, 39 where Ag NPs were synthesized with a similar experimental technique differing in the capping agents used. In that work, anionic, cationic, non-ionic and zwitterionic capping agents were adopted and an unusual efficiency of non-ionic species was detected, in some cases even higher than typical of ionic ones.…”
Section: Ag Np Synthesis By the Iwm Processsupporting
confidence: 88%
See 1 more Smart Citation
“…The smallest diameters are obtained for Ag NPs stabilized with fructose, with an estimated average value of 9.5 nm, while it amounts to 11.1 nm for mannitol-capped Ag NPs. Both values are comparable with those obtained in another study, 39 where Ag NPs were synthesized with a similar experimental technique differing in the capping agents used. In that work, anionic, cationic, non-ionic and zwitterionic capping agents were adopted and an unusual efficiency of non-ionic species was detected, in some cases even higher than typical of ionic ones.…”
Section: Ag Np Synthesis By the Iwm Processsupporting
confidence: 88%
“…These aspects have been discussed in a previous work. 39 At this point, the open research questions are essentially focused on two main aspects, the second of which follows the first one: a) Can the carbohydrates here employed act as a stabilizer for the Ag NPs formed, according to the top-down methods presently described? b) Do the carbohydrates play a role in promoting the physical disaggregation of the bulky Ag metal in the first step of the process?…”
Section: Reaction Chemistry and Engineering Papermentioning
confidence: 99%
“…A crucial aspect in bead milling processes is the balancing between the size of the grinding beads and that of the particles to be treated, as a relatively large inter-bead space at a close-packing configuration may determine a dramatic reduction of milling efficiency [ 22 ]. To this aim we performed further simulations by varying the dimension and number of the grinding beads, to reproduce different bed configurations.…”
Section: Resultsmentioning
confidence: 99%
“…Previous investigations have shown that this configuration avoids the stirring bar to get stuck, whereas such phenomenon can occur by increasing the number of spheres or their dimension. The detailed description of the experimental apparatus mentioned above can be found in Reference [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…He showed that AgNPs with an average size of 6−10 nm can be ball-milled using a cryomill at −160 °C with an argon flow rate of 2 L/min. 30 Reverberi et al 31 also used a magnetically driven milling method to synthesize AgNPs with the same shape and size by grinding the metal precursor consisting of Ag spheres. Their method is cost-effective and can be performed in liquid solvents under ambient conditions, where other capping agents could be dissolved to damp particle agglomeration.…”
Section: Fundamentals and Fabrication Of Nmnpsmentioning
confidence: 99%